2010
DOI: 10.1177/1941406409359195
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors That May Predispose Premature Infants to Increased Incidence of Necrotizing Enterocolitis

Abstract: The objective of this study was to determine if there are any common “risk factors” that could assist clinicians in identifying premature infants who are at greater risk for developing necrotizing enterocolitis (NEC). This was a retrospective study of infants admitted to the neonatal intensive care unit at Children’s Hospital of Illinois, Peoria. In total, 384 charts were reviewed. Seventy-eight infants diagnosed with NEC were compared to 246 infants who did not have NEC. Maternal risk factors, infant demo-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…We found that male gender was a highly predictive parameter for intestinal perforation associated with NEC compared to only NEC. There are only a few studies where male gender has been significantly associated to increased risk of NEC [ 36 , 38 ] or not [ 39 ]. Duci et al reported that gender was not statistically significant when comparing patients with NEC treated medically vs. NEC requiring surgery [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that male gender was a highly predictive parameter for intestinal perforation associated with NEC compared to only NEC. There are only a few studies where male gender has been significantly associated to increased risk of NEC [ 36 , 38 ] or not [ 39 ]. Duci et al reported that gender was not statistically significant when comparing patients with NEC treated medically vs. NEC requiring surgery [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of NEC varies from 0.5 to 5 infants per 1000 live births with a mortality rate of 10–50% [10].…”
Section: Discussionmentioning
confidence: 99%
“…18 Prolonged rupture of membranes, a common antecedent to chorioamnionitis, has been associated with NEC across several studies spanning several decades. 1921 While maternal infection may increase NEC risk for the infant, maternal antibiotic treatment does not appear to increase risk and may, in fact, decrease it. Data from a prospective, observational microbiome study found a reduced risk of NEC if maternal antibiotics were given (OR 0.28, 95% CI 0.14–0.56, 580 infants).…”
Section: Maternal and Antenatalmentioning
confidence: 99%